Fully-coupled hydrologic processes for modeling landscape evolution. (August 2016) - Zhang, Yu; Slingerland, Rudy; Duffy, Christopher
Abstract: Although current landscape evolution models can predict landscapes with specific concave-convex slopes, regolith thicknesses, drainage densities and relief, these models rarely include realistic groundwater and overland flows, and channel-hillslope interactions. To overcome the potential drawbacks, this study couples hydrologic processes with hillslope and channel sediment transport processes to form a new hydrologic-morphodynamic model (LE-PIHM) for regolith formation and landscape evolution. Two scenarios with and without groundwater flow are presented to demonstrate the importance of this coupling. Comparison of the steady state landforms indicates that hillslopes are steeper and relief is higher with groundwater flow. The sensitivity of the solution to mesh geometry is tested and it is shown that model simulations maintain the characteristic features of a landscape over a reasonable range of maximum area and minimum interior angle. To predict long-term landscape change, a morphological acceleration technique is presented and a method for choosing an optimal morphological scale factor is introduced. Highlights: A new fully-coupled hydrologic-morphodynamic model is presented. Slopes and relief of the landscape shows the importance of coupling subsurface flow. Erosion rate reaches the peak at the moment of exfiltration and then decreases. A morphological acceleration technique is introduced for morphological simulation. Numerical experiments shows the existence of an optimal morphological scale factor.